The kinin B(1) receptor contributes to the cardioprotective effect of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers in mice - Xu, Jiang (2008)
Recent studies have shown that inhibition of angiotensin-converting enzyme (ACE) or angiotensin II receptors causes upregulation of the B(1) receptor (B(1)R). Here we tested the hypothesis that activation of the B(1)R partly contributes to the cardiac beneficial effect of ACE inhibitor (ACEi) and angiotensin II receptor blockers (ARB). B(1)R knockout mice (B(1)R(−/−)) and C57Bl/6J (wild-type control animals, WT) were subjected to myocardial infarction (MI) by ligating the left anterior descending coronary artery. Three weeks after MI, each strain of mice was treated with vehicle, ACEi (ramipril, 2.5 mg kg(−1) day(−1) in drinking water) or ARB (valsartan, 40 mg kg(−1) day(−1) in drinking water) for 5 weeks. We found that: (1) compared with WT mice, B(1)R(−/−) mice that underwent sham surgery had slightly but significantly increased left ventricular (LV) diastolic dimension, LV mass and myocyte size, whereas systolic blood pressure, cardiac function and collagen deposition did not differ between strains; (2) MI leads to LV hypertrophy, chamber dilatation and dysfunction similarly in both WT and B(1)R(−/−) mice; and (3) ACEi and ARB improved cardiac function and remodelling in both strains; however, these benefits were significantly diminished in B(1)R(−/−) mice. Our data suggest that kinins, acting via the B(1)R, participate in the cardioprotective effects of ACEi and ARB.